Identification of gastrointestinal helminths infection from goats isolated in a farm in Kuantan, Pahang, Malaysia - Mohd Azlan, Mawaddah; Mat Yusof, Afzan; Mohammad, Mardhiah (Penerbit UTM Press, 2019)
Livestock is a group of domesticated animal that is reared in an agricultural setting. It usually served as a source of income for most peoples in Malaysia. However, the productions of this livestock especially goats have been decreasing due to the occurrence of gastrointestinal helminths infection. The aim of this study was to identify the presence and species of gastrointestinal helminths from 120 fecal samples collected directly from the rectum of goats from a farm located in Kuantan, Pahang. Firstly, the physical observation was evaluated on all goats. Then, their fecal sample was examined within 96 hours using Formal-ether Sedimentation method for the morphological characteristics identification of gastrointestinal helminthic species under the microscope. This study has identified the majority of goats with a good physical condition, that they have no sign of blood loss and have appropriate body frame. However, the microscopic identification has revealed 89 from the total samples positive with gastrointestinal helminths species while 76 of the positive showed presence of mixed species. The species found were Haemonchus contortus, Trichostrongylus spp., Trichuris ovis, Oesophagostomum spp., Ostertagia spp., and Strongyloides papillosus. This high infection of gastrointestinal helminths observed in goats is related to an impaired immune system, poor farm management, and uncontrolled anthelmintic treatment. The presence of various species of gastrointestinal helminths within a goat is an important cause of morbidity and loss of production. Therefore, this study suggested the need for an effective system of management, diagnosis and appropriate treatment that can reduce the risk of infection and increase the productivity of the animals. ********************************************************